Variation of venous admixture, SF6 shunt, PaO2, and the PaO2/FIO2 ratio with FIO2. - Whiteley, J; Gavaghan, D; Hahn, C (2002)
BACKGROUND: Measures of impairment of oxygenation can be affected by the inspired oxygen fraction. METHODS: We used a mathematical model of an inhomogenous lung to predict the effect of increasing inspired oxygen concentration (FIO2) on: (1) venous admixture (Qva/Qt); (2) arterial oxygen partial pressure (PaO2); (3) the PaO2/FIO2 index of hypoxaemia; and (4) sulphur hexafluoride (SF6) retention (often taken to be true right-to-left shunt). This model predicts whether or not atelectasis will occur. RESULTS: For lungs with regions of low V/Q, increasing the inspired oxygen concentration can cause these regions to collapse. In the absence of atelectasis, the model predicts that Qva/Qt will decrease and arterial oxygen partial pressure increase as FIO2 is increased. However, when atelectasis occurs, Qva/Qt rises to a constant value, whilst PaO2 falls at first, but then begins to rise again, with increasing FIO2. The SF6 retention increased markedly in some cases at high FIO2. CONCLUSIONS: Venous admixture will estimate true right-to-left shunt at high FIO2, even when oxygen consumption is raised. This model can explain the way that the Pa/Fl ratio changes with increasing inspired oxygen concentration.